Determinants of Depression Severity among Adults in Eastern Shan State: An Ordered Logistic Regression Analysis - Thein Myint Twin; Kyaw Min Htike; Roshan Kumar Mahato (International Journal of Public Health Asia Pacific, 2026)
Background: Depression is a major global public health concern, particularly in low- and middle-income countries where access to mental health services is limited. In Myanmar, the burden of mental health disorders is increasing especially in conflict-affected regions such as Eastern Shan State. While prevalence studies exist, limited research has explored the determinants of depression severity using robust statistical approaches. Objective: This study aimed to examine the factors associated with increasing severity of depressive symptoms among adults in Eastern Shan State, Myanmar using a generalized ordered logistic regression model. Methods: An analytical cross-sectional study was conducted among 448 adults aged 18–59 years in Eastern Shan State. A structured interviewer-administered questionnaire was used to collect data on demographic, behavioural and psychosocial factors. Validated tools including CESD-10, GAD-7, SPRINT and MPSS were used. An ordered logistic regression model (ologit in STATA) was applied to identify factors associated with increasing severity of depressive symptoms, allowing relaxation of the proportional odds assumption where necessary. Results: Based on the CES-D 10 scale, 53.6% (95%CI:48.92-58.16) of participants had mild or no depressive symptoms, 35.9% (95%CI:31.61-40.50) had moderate symptoms and 10.5% (95%CI:7.97-13.70) had severe depressive symptoms. Multivariable ordinal logistic regression identified individuals who were unemployed (AOR = 1.78, 95%CI:1.17-2.71), had inadequate financial status (AOR = 2.44, 95%CI:1.65-3.62), reported poor self-rated health (AOR = 3.01, 95%CI:1.89-4.82), trauma exposure (AOR = 1.88, 95%CI:1.26-2.82), forced displacement (AOR = 1.94, 95%CI:1.07-3.54), spending more than two hours daily on socio-political news (AOR = 2.34, 95%CI:1.57-3.50) and poor sleep efficiency (AOR = 3.07, 95%CI:1.49-6.35) were significantly associated with greater severity of depressive symptoms. Conclusion: The study highlights key socio-behavioural and psychological determinants of depression severity in a conflict-affected population. Integrated mental health services targeting these risk factors are urgently needed to address the burden of depression in Eastern Myanmar and similar fragile contexts.